The Islamic Education Paradigm of Muhammad Iqbal’s Philosophy - Suripto (Tarbiyah Departement collaboration with AMCA, 2020)
Mohammad Iqbal is a Muslim of modern philosopher which greatly affects the world of education up to now. His concept about ego is the basic stand for his all of concept building. In addition, the Muhammad Iqbal’s basic of Islamic education concept are creative, dynamic, innovative and full of vitality. Based on his basic view about human especially his philosophy concept about ego, a thought about Islamic education is dynamic, innovative, and full of vitality. a). The essence of Iqbal’s Islamic education is all power or process done continually. They help to improve one’s individuality based on Islamic teaching in order to be ready in entering the world’s civilization which is full of dynamics and changings. b). The aim of Islamic education is the realization of one’s individuality perfectness to be an insan kamil. c). According to Iqbal the phases of Islamic education are obey upon the laws, self authority and God leadership. d). The material of Iqbal’s Islamic education emphasizes on the fusion of religion studies, cultural history, science and physics, psychology, metaphysics, social studies and literature. e). The education methods offered by Iqbal are experiment, trial and error, project and social structure. The paradigm used within Iqbal’s philosophy concept is constructive paradigm. Meanwhile the values within the construction of Iqbal’s Islamic education are: God oneness, moral, intelligence, and social education values.